From connectivity via intelligence toward sustainability? Maturity of shopfloor automation technology in the manufacturing industry - Reichenstein, Tobias; Reich, Christina Stefanie; Hoffmann, Kilian; Franke, Jörg (Procedia CIRP, 2024)
The manufacturing industry is experiencing a significant transformation driven by digital technologies, Industry 4.0 concepts, and the potential for sustainable practices. This research presents an overview of the manufacturing industry, focusing on the design of manufacturing systems, digital transformation, and sustainability, identifying the gap between technological advancements and their application in industrial settings. In order to examine this, a panel survey of 899 industrial participants was conducted. This analysis assesses the potential for automation and digital factory implementation alongside the dedication for sustainability in the manufacturing industry. The findings indicate that while research has advanced in these areas, practical applications in the manufacturing industry still lag behind, particularly in terms of technology readiness levels and data implementation for automation. This paper serves as a foundation for future research, providing insights into technologies ready for industrial implementation and identifying areas requiring further optimization and study. Therefore, a matrix is presented that aids in selecting or strategizing technology utilization during the design of manufacturing systems. However, this research primarily focused on technological aspects, recommending future research to explore the interplay between organizational, human related factors, and technology to design manufacturing systems successfully with respect to sustainabilit
Keywords: Industry 4.0; shopfloor automation; digital factory; digital twin; sustainability; Design methodology; tools; technologies